1992
DOI: 10.1007/bf00048064
|View full text |Cite
|
Sign up to set email alerts
|

Active cell death in hormone-dependent tissues

Abstract: Active cell death (ACD) in hormone-dependent tissues such as the prostate and mammary gland is readily induced by hormone ablation and by treatment with anti-androgens or anti-estrogens, calcium channel agonists and TGF beta. These agents induce a variety of genes within the hormone-dependent epithelial cells including TRPM-2, transglutaminase, poly(ADP-ribose) polymerase, Hsp27 and several other unidentified genes. Not all epithelial cells in the glands are equally sensitive to the induction of ACD. In the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
145
1
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 255 publications
(148 citation statements)
references
References 217 publications
(227 reference statements)
1
145
1
1
Order By: Relevance
“…During tumor promotion by NAF, the excess of cell proliferation over apoptosis increased with advancing only in a few models using hormone-dependent tumors. [29][30][31] Here we provide-to our knowledge, for the first time-funcmalignancy (Fig. 5), as shown above for spontaneous carcinogenesis.…”
Section: Effects Of Naf Treatment On Normal Liver and On Tumormentioning
confidence: 89%
“…During tumor promotion by NAF, the excess of cell proliferation over apoptosis increased with advancing only in a few models using hormone-dependent tumors. [29][30][31] Here we provide-to our knowledge, for the first time-funcmalignancy (Fig. 5), as shown above for spontaneous carcinogenesis.…”
Section: Effects Of Naf Treatment On Normal Liver and On Tumormentioning
confidence: 89%
“…It was suggested that clusterin protects the apoptotic cell from complement fixation during the time of membrane blebbing and cytoplasmic condensation (Tenniswood et al, 1992). Lack of correlation between clusterin expression and apoptosis was demonstrated in other systems, such as neural death during development (Garden et al, 1991), and several inducible models of apoptosis (Pearse et al, 1992;reviewed in Rosenberg et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…2 Because it has been studied independently by a number of laboratories and in different systems, it has been given various names, such as SGP-2, clusterin, apolypoprotein J, SP 40 -40, complement lysis inhibitor, gp80, glycoprotein III, and T64. 3 The human homologue of clusterin is comprised of 449 amino acids with two 40-kd subunits (␣ and ␤) joined by a unique five disulfide bond motif. 4 The protein precursor is encoded on a single 2 kb mRNA that is transcribed from a single copy gene located on chromosome 8 (8p21).…”
mentioning
confidence: 99%
“…6 Thus, clusterin mRNA has been widely used as a genetic marker of apoptotic cell death. 3 In hormone-dependent tissues, such as the prostate and the mammary gland, clusterin expression is induced after hormone ablation. 10,11 However, these studies did not analyze which cells account for the rise in clusterin gene expression, the cells undergoing apoptosis or those destined to survive.…”
mentioning
confidence: 99%